Diseño e implementación de un sistema de riego por aspersión fijo en chirinche, grupo sabia nueva, parroquia Mulalillo del cantón salcedo provincia de Cotopaxi - Chamba Melo, Jonathan Javier (2012)
This research was carried out in the community of Chirinche Mulalillo Parish, Salcedo Canton, Cotopaxi Province. We found a big problem in the cultivation process. The cause is that there isn´t an irrigation system and it does not allow the development of agricultural area. The project is to design and to implement a system of fixed sprinkler irrigation for the benefit of community people. In addition to analyze how their products grow and after an valuation in combination with the study, it determines the supplies indispensables, budgets and technical report. In addition, it determined that it is important the Implementation of the sprinkler system on three parcels which have a reservoir. Finally, we got the following conclusions: the project is technically feasible, as it has a wealth of water suitable for this type of irrigation technology. The topography permits obtaining a natural pressure of the liquid. It reduces costs in the implementation process. The irrigation system employed in the community, will optimize water use, and contribute in the process of cultivation and development of the beneficiaries.